Analisis Komparatif Karakteristik Tegangan Output Cúk Converter dan Single-Ended Primary Inductance Converter (SEPIC) Terhadap Variasi Duty cycle - effendi effendi; Farid Widiyanto (J-Innovation, 2026)
This study aims to comparatively analyze the output voltage characteristics of the Cúk converter and the Single-Ended Primary Inductance Converter (SEPIC) under varying duty cycle conditions. Both converters were designed using identical parameters, including a 12 V input voltage, 50 Ω resistive load, 1 mH inductors for L1 and L2, a 47 µF coupling capacitor, a 470 µF output capacitor, and a switching frequency of 25 kHz. The evaluation was carried out through simulation by varying the duty cycle from 0.1 to 0.9. The analysis focused on output voltage variation, transient waveform response, overshoot, settling time, and frequency-domain characteristics using Fast Fourier Transform (FFT). The simulation results show that increasing the duty cycle significantly increases the output voltage of both converters in a nonlinear manner. The output voltage of the Cúk converter increased from 1.8748 V to 108.3203 V, while the SEPIC output voltage increased from 1.8484 V to 108.1663 V. Both converters operate in step-down mode at low duty cycle s and step-up mode at high duty cycle s. Although both converters produce relatively comparable output voltage levels, SEPIC demonstrates better performance in terms of output voltage quality, as indicated by lower oscillation amplitude, faster settling time, lower AC components, reduced ripple, and smoother harmonic spectrum. In contrast, the Cúk converter exhibits more dominant ripple and switching harmonics, particularly at low to medium duty cycle s. Therefore, SEPIC is more suitable for applications requiring a stable, clean, and low-ripple DC output voltage.